2013
DOI: 10.1177/0272431613494007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Paternal Psychological Control as Moderators of the Link between Peer Attitudes and Adolescents’ Risky Sexual Behavior

Abstract: Maternal and paternal psychological control, peer attitudes, and the interaction of psychological control and peer attitudes at age 13 were examined as predictors of risky sexual behavior before age 16 in a community sample of 181 youth followed from age 13 to 16. Maternal psychological control moderated the link between peer attitudes and sexual behavior. Peer acceptance of early sex predicted greater risky sexual behaviors, but only for teens whose mothers engaged in high levels of psychological control. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…Youth parented with greater psychological control at age 13 were significantly less likely to exhibit autonomy and relatedness during disagreements with romantic partners at age 18, and then remained significantly behind their counterparts in expressing autonomy and relatedness with romantic partners at age 21. Psychological control has long been theorized to undermine the development of autonomy and relatedness, and has been found to predict many markers of poor autonomy and relatedness skills, including hostility and susceptibility to peer pressure (Allen, Chango, Szwedo, Schad, & Marston, ; Allen et al., ; Barber, ; Oudekerk et al., ; Schaefer, ). Findings herein extend past research by identifying a direct, observable, and longitudinal connection between parent psychological control and decreasing ability over time to establish autonomy and relatedness with friends and romantic partners.…”
Section: Discussionmentioning
confidence: 99%
“…Youth parented with greater psychological control at age 13 were significantly less likely to exhibit autonomy and relatedness during disagreements with romantic partners at age 18, and then remained significantly behind their counterparts in expressing autonomy and relatedness with romantic partners at age 21. Psychological control has long been theorized to undermine the development of autonomy and relatedness, and has been found to predict many markers of poor autonomy and relatedness skills, including hostility and susceptibility to peer pressure (Allen, Chango, Szwedo, Schad, & Marston, ; Allen et al., ; Barber, ; Oudekerk et al., ; Schaefer, ). Findings herein extend past research by identifying a direct, observable, and longitudinal connection between parent psychological control and decreasing ability over time to establish autonomy and relatedness with friends and romantic partners.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, parenting factors also may influence risky behaviors both directly and indirectly by affecting their children's peer clusters (McKinney, Milone, & Renk, ; Oetting et al., ). In particular, evidence has suggested parental control behaviors may influence peer selection (Oudekerk et al., ; Tilton‐Weaver, Burk, Kerr, & Stattin, ; Walters, ).…”
Section: Parental Overprotection and Rsbmentioning
confidence: 99%
“…(), parental control behaviors, including monitoring and communicating disapproval, decreased the likelihood of selecting deviant peers and their influence on the adolescents. However, another study suggested parental control increased the influence that deviant peers had on the likelihood to engage in RSB (Neppl et al., ; Oudekerk et al., ). Specifically, peer attitudes on early sexual behavior exclusively predicted risky sexual behavior when parents exerted high levels of psychological control (Oudekerk et al., ).…”
Section: Parental Overprotection and Rsbmentioning
confidence: 99%
See 2 more Smart Citations